Evaluation of Investment and Return in Informal Sector: A Case of Chitwan District - Dhakal, Ramchandra (Tribhuvan University Journal, 2013)
Developing counties, like Nepal is still in tense to maintain the level of political stability, economic growth, development, and employment which are the main issues in one side of the economy and on the other, the majority of the people find shelter in the informal sector in the absence of sluggish growing formal sector. Most of the people are engaged in informal economies that have created varying effects on them in terms of employment and income generations. The latter seems to be determined mainly by the household property, level of literacy, the number of persons employed in any unit and investment. However, there is no apparent differentiation in the income earnings between males and females, the latter seems to be more efficient and articulate in many ways. Income earnings have been higher in the urban location than that of the rural sector. Income level and the determining factors seem to vary among different location and sexes. This study tries to compare the nature and characteristics of informal sector both at national as well as international levels. The government must play effective policy as well as to uplift informal economy for the economic development as a whole. To identify the informal sector properly in Nepal, a national wide survey that covers overall aspects should be considered before taking any step.